2017
DOI: 10.1167/iovs.16-20095
|View full text |Cite
|
Sign up to set email alerts
|

Visual Perception and Reading: New Clues to Patterns of Dysfunction Across Multiple Visual Channels in Developmental Dyslexia

Abstract: Our evidence stands in favor of a differential visual channel deficit in children with developmental dyslexia and contributes to the debate on the pathophysiology of reading impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…And this area is dominated by magnocellular signals (Maunsell et al, 1990). Studies have shown that subjects with dyslexia have lower motion sensitivity than have controls (Benassi et al, 2010;Gori, Seitz, Ronconi, Franceschini, & Facoetti, 2016;Rodrigues et al, 2017). Study by Boets, Vandermosten, Cornelissen, Wouters, and Ghesquière (2011) support the view that coherent motion is related to reading.…”
Section: Introductionmentioning
confidence: 90%
“…And this area is dominated by magnocellular signals (Maunsell et al, 1990). Studies have shown that subjects with dyslexia have lower motion sensitivity than have controls (Benassi et al, 2010;Gori, Seitz, Ronconi, Franceschini, & Facoetti, 2016;Rodrigues et al, 2017). Study by Boets, Vandermosten, Cornelissen, Wouters, and Ghesquière (2011) support the view that coherent motion is related to reading.…”
Section: Introductionmentioning
confidence: 90%
“…In this context, it is necessary to eliminate the underlying cause of children's ability to cope with reading difficulties, in other words, it is necessary to ensure success in reading by transferring the problems they experience in visual perception to other perception areas. It is emphasized that children with dyslexia experience problems in visual perception (Rodrigues et al, 2017).…”
Section: Types Of Specific Learning Difficultymentioning
confidence: 99%
“…[ 8 9 10 ] However, further studies have revealed that sensory and visual perceptual dysfunctions might play a role. [ 11 ] Fluent reading requires rapid processing of visual information, including spatial and temporal data. [ 12 13 ] It has been proposed that dyslexic children might have a deficit in rapid processing of visual and auditory modalities.…”
Section: Introductionmentioning
confidence: 99%